Teaching professionalism in cadaver dissection: medical students' perspective - Mafinejad, Mahboobeh Khabaz; Taherahmadi, Mohammad; Asghari, Fariba; Mehran Nia, Kobra; Mehrpour, Saeeid Reza; Hassanzadeh, Gholamreza; Farahani, Parisa; Hosseini Dolama, Reza (Journal of medical ethics and history of medicine, 2021)
This study was designed to facilitate freshman medical students’ adaptation to the dissection room and familiarize them with the related ethical codes. Single-group post-test design research was conducted at Tehran University of Medical Sciences in 2018 - 2019. The program began with a brief explanation of the necessity of the subject, and after a documentary film was shown, the principles of professional and ethical behaviors in the dissection room were discussed by a panel of experts. In the end, a valid and reliable evaluation questionnaire (Cronbach's alpha coefficient = 0.89) was distributed among the students. A total of 129 questionnaires were completed and returned. Overall, 94.4% of the students believed that the program provided an excellent opportunity to reflect on professional behaviors during practical anatomy sessions. In addition, 92.8% of the students believed that they would use the ethical points mentioned in the program in the future. Content analysis of the open questions produced three main categories: "motivating learning", "application of theory in practice" and "changing the attitude toward responsibility". The results indicate that adequate preparation for cadaver dissection sessions and learning about professional behavior codes in the first exposure can help medical students to better understand the principles of professional behaviors.